Investigation on the oxide-oxide galvanic displacement reactions employed in the preparation of electrocatalytic layers. (1st May 2020) - Comisso, Nicola; Rancan, Marzio; Armelao, Lidia; Barison, Simona; Cattarin, Sandro; Guerriero, Paolo; Mattarozzi, Luca; Musiani, Marco; Vázquez-Gómez, Lourdes; Verlato, Enrico
Abstract: Galvanic displacement reactions between sacrificial oxide layers and metal cations, leading to the formation of secondary oxide layers, have been studied with the aim of collecting new experimental evidence on their mechanism. The study has been carried out by combining electrochemical methods, SEM-EDS and XPS depth profiling. Both porous and compact PbO2 layers have been used as sacrificial oxides and reacted, in different experiments, with: (i) a single low-valent cation, (ii) two cations in sequential exchange reactions or (iii) two cations simultaneously. The experimental results converged to show (i) a lack of correlation between the reaction driving force and the secondary oxide growth rate, (ii) the incorporation of cations from solution at the secondary oxide/electrolyte interface, (iii) the transport of Pb species through the growing secondary oxide layer and (iv) a major effect of mass transport on the growth rate. Graphical abstract: Image 1 Highlights: The mechanism of galvanic displacement between oxides has been studied. Secondary and tertiary oxides were grown onto compact and porous PbO2 . Secondary oxides contained significant amounts of Pb. The growth rate of secondary oxides was not governed by the reaction driving force. Diffusion through the growing secondary oxide was rate determining.